[OP.8A.06] PULSATILE STRETCH ALTERS AMYLOID PRECURSOR PROTEIN EXPRESSION AND NITRIC OXIDE SIGNALLING IN HUMAN CEREBRAL ENDOTHELIAL CELLS PRE-EXPOSED TO GLYCOSPHINGOLIPID INHIBITION. (September 2017) - Gangoda, S.; Veppala, B.; Butlin, M.; Gupta, V.; Chung, R.; Avolio, A.
Abstract : Objective: Amyloid β (Aβ) deposits that arise from amyloid precursor protein (APP) are a hallmark of Alzheimer's disease (AD). Elevated pulsatility of arterial pressure and deregulation of ceramide and nitric oxide (NO) metabolism are associated with AD. Glycosphingolipid inhibitors that inhibit the production of the enzyme glucosylceramide synthase by blocking ceramide glycosylation are known to increase gamma secretase-mediated-Aβ release. This study investigates whether pulsatile stretch of human cerebral microvascular endothelial cells (hCMEC) pre-treated with the glycosphingolipid inhibitor, D-threo-1-Phenyl-2-decanoylamino-3-morpholino-1-propanol (D-PDMP), alters expression and/or phosphorylation of APP and endothelial NO synthase (eNOS). Design and method: hCMECs were pre-treated with 20 μM D-PDMP for 2 hours prior to 15% cyclic stretch for 18 hours at 1 Hz (n = 7–8). Protein expression and phosphorylation (phospho-eNOS, Ser1177) were quantified using western blots. Results were analyzed using one way ANOVA (mean ± SEM, % control). Results: APP expression increased significantly in response to stretch in ECs pre-treated with D-PDMP (170.2 ± 27%, p < 0.01) compared to cells stretched without pre-treatment (114.5 ± 23%). eNOS phosphorylation was down-regulated in ECs subjected to stretch (9.9 ± 4%) compared to vehicle control (100.0 ± 0%, p < 0.0001) and D-PDMP-treated-static control (107.0 ± 17%, p < 0.01). In ECs pre-treated with D-PDMP prior to stretch, phospho-eNOS levels decreased significantly (40.3 ± 15%) compared to vehicle control (100.0 ± 0%, p < 0.05) and PDMP-treated-static control (107.0 ± 17%, p < 0.01). Conclusions: APP expression increased in cerebral ECs pre-treated with D-PDMP after being exposed to cyclic stretch. eNOS phosphorylation was down-regulated by cyclic stretch. D-PDMP pre-treatment appeared to have a restoring effect on phospho-eNOS, although it did not statistically significance. Glycosphingolipid inhibition with D-PDMP and cyclic stretch may lead to ceramide accumulation thereby increasing the Aβ load. This can affect NO production and modulation of Aβ deposits.